2017
DOI: 10.1589/jpts.29.1561
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ground reaction force in sit-to-stand movement and lower extremity function in community-dwelling Japanese older adults using long-term care insurance services

Abstract: [Purpose] The purpose of this study was to investigate which of the four chair-rising methods has low-load and the highest success rate, and whether the GRF parameters in that method are useful for measuring lower extremity function among physically frail Japanese older adults. [Subjects and Methods] Fifty-two individuals participated in this study. The participants voluntarily attempted four types of Sit-to-stand test (one variation without and three variations with the use of their arms). The following param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Our results on the evaluation of the association between power score (F/wt) or speed score (RFD/wt) and mCHS-defined physical frailty are consistent with those of a previous study, which reported the association between RFD/wt and physical performance (TUG and 5-min walk test) [ 16 ] and between low F/wt and fall risk [ 15 ]. Furthermore, F/wt and RFD/wt can accurately detect sarcopenia [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results on the evaluation of the association between power score (F/wt) or speed score (RFD/wt) and mCHS-defined physical frailty are consistent with those of a previous study, which reported the association between RFD/wt and physical performance (TUG and 5-min walk test) [ 16 ] and between low F/wt and fall risk [ 15 ]. Furthermore, F/wt and RFD/wt can accurately detect sarcopenia [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…The maximum GRF/body weight (F/wt), rate of force development/body weight (RFD/wt), and lateral load sway during sit-to-stand motion are used to indicate power, speed, and balance of physical performance, respectively. The power score (F/wt) is associated with disabilities in performing the activities of daily living [ 16 ] and the incidence of falls [ 15 ], while the speed score (RFD/wt) is related to the TUG time and walking speed [ 14 ]. Low power, speed, and balance scores are associated with high serum growth differentiation factor-15 levels [ 17 ]; however, a few studies have reported the association between the dynamic parameters in sit-to-stand motion and incidence of frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, also the standardisation of posture at the beginning of the trials could have restricted the applicability of the presented evidence. Both the setting of the starting position and the individuals' characteristics influence the STS motion strategy and consequently, the value of the vertical GRF and the successful outcome of the movement [20], [43], [44]. Hence, future studies should investigate if the presence of different conditions (e.g., different uses of the arms during the rising, different fatigue condition of the participants etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The standardisation of posture at the beginning of the trials and the homogeneity of the sampled population in HAR1 and HAR2 could have restricted the applicability of the presented evidence. Both the setting of the starting position and the individuals' characteristics in uence the STS motion strategy and consequently, the value of the vertical GRF and the successful outcome of the movement [20,43,44]. Hence, the presented algorithm must be tested across a different set of initial conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%